The interactive effects of the sulphite ion pH dissolved oxygen and milling environment on the flotation of chalcopyrite and galena from black mountain ore. - Ross, Victor Emul (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Ing.) -- University of Stellenbosch, 1983.